Sjogren’s Syndrome and TAM Receptors: A Possible Contribution to Disease Onset - Richard Witas; Ammon B. Peck; Julian L. Ambrus; Cuong Q. Nguyen (Journal of Immunology Research)
Sjogren’s syndrome (SS) is a chronic, progressive autoimmune disease featuring both organ-specific and systemic manifestations, the most frequent being dry mouth and dry eyes resulting from lymphocytic infiltration into the salivary and lacrimal glands. Like the related autoimmune disease systemic lupus erythematosus (SLE), SS patients and mouse models display accumulation of apoptotic cells and a Type I interferon (IFN) signature. Receptor tyrosine kinases (RTKs) of the Tyro3, Axl, and Mer (TAM) family are present on the surface of macrophages and dendritic cells and participate in phagocytosis of apoptotic cells (efferocytosis) and inhibition of Type I IFN signaling. This review examines the relationship between TAM receptor dysfunction and SS and explores the potential contributions of TAM defects on macrophages to SS development.